Pasar Pagi Bagi Orang Miskin: Peran BUMDES Dalam Mengatasi Kemiskinan di Desa Gemawang, Kabupaten Temanggung - Riza Rofiatul Muna; M. Ali Sofyan (IAIN Syekh Nurjati Cirebon, 2023)
This research aims to (1) find out how community development through BUMDES morning market as an effort to alleviate poverty in Gemawang Village, Temanggung Regency. (2) The strategy applied by BUMDES Gemawang in poverty alleviation efforts in Gemawang Village, Temanggung Regency.This research is a qualitative research with a case study approach. The object of this research is the morning market at BUMDES Gemawang. The data in this study were obtained through primary and secondary data sources. Primary sources include the results of interviews from the Gemawang Village government, morning market traders, and traveling vegetable traders. While secondary data sources include journals, books, and articles related to community empowerment.The data that has been collected is then analyzed so that the research results are obtained that (1) community empowerment through the morning market as a means of poverty alleviation managed by BUMDES Gemawang is able to change the living conditions of poor households to a higher level of welfare. (2) The strategy of BUMDES Gemawang in an effort to alleviate poverty in Gemawang Village is by creating a morning market, creating traders and regular consumers in the morning market. They are given capital facilities so that they can develop their lives in the morning market. BUMDES creates conditions for healthy competition among traders by applying the concept of one trader, one product. Vegetable traders also get the distribution of marketing areas to traveling vegetable traders. With the strategy implemented by BUMDES Gemawang, it is able to reduce poverty in Gemawang Village, Temanggung Regency.